Montenegro : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
This 2012 Article IV Consultation highlights that three years after the sudden end of Montenegro's boom, there has been considerable progress toward recovery. Fiscal imbalances have proved difficult to rein in, reflecting a large fall in revenue after the collapse of the boom. Executive Directors have commended the authorities' efforts to stabilize the economy, and welcomed the progress made since the financial crisis. Directors have also recognized the sizable public expenditure adjustment over the past few years, but underscored the need for further high-quality deficit reducing measures.